Drift potential of UAV with adjuvants in aerial applications - Wang, Xiaonan; He, Xiongkui; Song, Jianli; Wang, Zhichong; Wang, Changling; Wang, Shilin; Wu, Ruochen; Meng, Yanhua (International Journal of Agricultural and Biological Engineering, 2018)
The reduction of pesticide aerial spraying drift is still one of the major challenges in modern agriculture. The aim of this study was to evaluate the drift potential of different types of unmanned aerial vehicle (UAV) and adjuvant products for reducing spray drift in aerial applications. Three types of UAV (3WQF120-12 and 3CD-15 fuel oil powered single-rotor UAV and HY-B-15L battery powered single-rotor UAV) were selected in this study with regular application parameters to compare each spray drift, and 3WQF120-12 fuel oil powered UAV was selected to quantify spray drift of 6 adjuvants dissolved in water under field conditions. Solutions were marked with brillant sulfoflavin dye (BSF) at 0.1%. Petri dishes and rotary impactors were used to collect airborne and sediment drift, respectively. Drift deposits were evaluated by spectrophotometry in order to quantify deposits. The results showed that when the flight height was 1.5-2.0 m above the crop at the flight speed of 4-5 m/s and the average wind speed of 1.63-1.73 m/s, 3WQF120-12 fuel oil powered UAV had lower drift potential than the other two types; DV0.5 and percentage of droplets with diameter ≤75 μm had very significant effects on spray drift percentage (p=0.01); the risk of drift in agricultural spraying could be significantly decreased not only by reducing the percentage of fine droplets but also by changing droplet spectra. Compared to water, Silwet DRS-60, ASFA+B, T1602, Break-thru Vibrant, QF-LY and Tmax could reduce by 65%, 62%, 59%, 46%, 42%, and 19% spray drift, respectively. when water without adjuvants were sprayed, 90% of drift droplets were located within a range of 10.1 m of the target area while with 0.8% Silwet DRS-60 adjuvant in water, the distance was shortened to 6.4 m. Keywords: spray drift, UAV, adjuvant, aerial application, drift potential evaluation, droplet size DOI: 10.25165/j.ijabe.20181105.3185 Citation: Wang X N, He X K, Song J L, Wang Z C, Wang C L, Wang S L, et al. Drift potential of UAV with adjuvants in aerial applications. Int J Agric & Biol Eng, 2018; 11(5): 54–58.